Dynamics of the Cadastre System: An Analysis of Challenges and Evaluation of Cadastre Implementation in Various Regions of Indonesia - Jonahar; Winoto, Joyo; Siregar, Hermanto; Lantara, I Wayan Nuka (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The implementation of the land cadastre system in Indonesia presents complex social, economic, and political implications. Despite its formal establishment, the system continues to face substantial challenges across various regions. The persistently low levels of land registration in certain areas underscore significant deficiencies in the system's execution, potentially heightening legal ambiguities and intensifying agrarian conflicts.Purpose: This study analyzes the issues of Indonesia's cadastre system and evaluates its implementation across various regions from the perspectives of land valuation, technology utilization, and stakeholder involvement.Design/methodology/approach: This study employs a qualitative approach. A total of 428 respondents, all of whom represent state officials within the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) at various levels, participated in the study. Data analysis was conducted using descriptive analysis by comparing the issues and implementation of the land cadastre system across the Western, Central, and Eastern regions of Indonesia.Findings/Result: The national cadastral system in Indonesia is plagued by five primary issues: overlapping land certificates, outdated and inaccurate land data, incomplete land registration, imprecise boundary mapping, and inconsistent coordinate measurements, which are also prevalent at the local level. These challenges are exacerbated by significant regional disparities, with Eastern Indonesia showing the lowest levels of land registration and technology adoption, in stark contrast to the more developed Western and Central regions.Conclusion: Indonesia's cadastral system faces critical challenges, including legal uncertainties, overlapping land certificates, and outdated data, which are exacerbated by significant regional disparities, particularly in Eastern Indonesia. To address these issues, it is essential to implement targeted reforms that enhance local government capacity, integrate advanced technology, and ensure public participation, thereby improving cadastral accuracy and equity across regions. These efforts are crucial for ensuring legal certainty, reducing agrarian conflicts, and supporting sustainable land development nationwide.Originality/value (State of the art): This study comprehensively maps the issues related to the cadastral system and evaluates the level of cadastral implementation across different regions of Indonesia, categorizing them into Western, Central, and Eastern regions. Keywords: cadastre system, cadastre challenges and issues, regional disparities, cadastral implementation, land valuation